A structural study of ALgE, transporter of alginate from Pseudomonas aeruginosa PAOI - Tan, Jingquan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
Pseudomonas aeruginosa is an opportunistic human pathogen that causes serious diseases in humans with immune system deficiencies, such as cystic fibrosis, wound infections, urinary tract infections, and blood stream infections (Bentzmann and Plésiat 2011). Biofilm formation plays an important role in the life cycle of P. aeruginosa to protect cells from adverse environment and facilitate the infection to hosts (Drenkard and Frederick 2002). In Membrane Structural and Functional Biology Group, we seek to control biofilm formation by reducing the secretion of one of its important components, alginate. For alginate to be secreted to the cell surface, the outer membrane protein, AlgE, is required as alginate transporter (Rehm et al. 1994). Thus, AlgE is chosen as the study target of this project.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.